The characteristics of family functioning with mentally ill children and adolescents - mandic gajic, gordana; Jelkić, Milica; Stojanović, Zvezdana; Djokić, Milan; Eror, Aleksandar; Kolundžija, Ksenija (Vojnosanitetski pregled, 2018)
Background/Aim. The family functioning and characteristics are the major risk factors in the genesis and persistence of mental disorders in children. The aim of this study was to evaluate the characteristics of functioning of family with mentally ill children and adolescents. Methods. This study explored 47 families with a child/adolescent suffering from mental disorders and 47 families of age matched healthy children/adolescents. The socio-demographic questionnaire, Social Adaptation Self-evaluation scale (SASS) and Family Adaptability and Cohesion Evaluation Scale (FACES III) (Olson, 1983) were completed by parents. Results. For all three FACES III dimensions multivariate analysis of variance (MANOVA) showed significant differences between groups ( Wilks λ = .887; F = 3.839; df = 3; p = 0.012). Univariate analysis results showed significant differences for cohesiveness F = 6.99 p = 0.001 and adaptability F = 10.07 p = 0 .001. The analysis of the social adaption (SASS) assessment showed that the mean score for clinical vs. non-clinical group was 39.66 ± 6.82 vs. 38.06 ± 8.44 without significant difference between groups (p = 0.32). The families of mentally ill children showed frequently lower socioeconomic status and education level, higher number of children per family, and broken home. Conclusion. The results suggested that cohesiveness and adaptability were significantly more prominent among families with mentaly ill children, but adaptation was similar to families with healthy children. It would be useful to evaluate adaptability, cohesiveness and adaptation of primary families when planning prevention and rehabillitation of mentally ill children and adolescent.